Conceptual background and bioenergetic/mitochondrial aspects of oncometabolism. - Galluzzi, Lorenzo; Kroemer, Guido (Methods in enzymology, 2014)
Volume 542 of Methods in Enzymology continues the legacy of this premier serial with quality chapters authored by leaders in the field. This new volume covers research methods providing a theoretical overview on metabolic alterations of cancer cells and a series of protocols that can be employed to study oncometabolism, in vitro, ex vivo and in vivo. Malignant cells exhibit metabolic changes when compared to their normal counterparts, owing to both genetic and epigenetic alterations. Although such a metabolic rewiring has recently been indicated as ""yet another"" general hallmark of ca.